Book Review:A. AYVAZYAN, The Armenian Military in the Byzantine Empire. Conflict and Alliance under Justinian and Maurice. [Alfortville] 2014, pp. 152. ISBN: 9782917329597 - MAKRYPOULIAS, Christos G. (Byzantina Symmeikta, 2016)
Book Review: A. Ayvazyan, The Armenian Military in the Byzantine Empire. Conflict and Alliance under Justinian and Maurice. [Alfortville] 2014, pp. 152. ISBN: 9782917329597